1996
DOI: 10.1145/250707.239131
|View full text |Cite
|
Sign up to set email alerts
|

Formal refinement patterns for goal-driven requirements elaboration

Abstract: Requirements engineering is concerned with the identification of high-level goals to be achieved by the system envisioned, the refinement of such goals, the operationalization of goals into services and constraints, and the assignment of responsibilities for the resulting requirements to agents such as humans, devices and programs. Goal refinement and operationalization is a complex process which is not well supported by current requirements engineering technology. Ideally some form of formal support should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0
9

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 22 publications
0
99
0
9
Order By: Relevance
“…clusterbased internal [11] (crime); [20] (organisation); [38], [45] (joint goals and intentions); [2], [37], [43] (epidemics) behavioural [34], [29], [41], [35], [28], [9] (organisation); [49], [57], [62] (ecological) temporally global agentbased internal [47], [24], [25], [64], [63], [48] (requirements); [31], [50], [59], [4], [21], [6], [7], [10], [12], [40] (verification) behavioural clusterbased internal [24], [25], [34], [29], [30], [41], [36], [18], [55], [64], [65] (requirements, enterprise); [43], [2], [37] (epidemics); [49], [57], …”
Section: Discussion and Classification Of Existing Modelsmentioning
confidence: 99%
“…clusterbased internal [11] (crime); [20] (organisation); [38], [45] (joint goals and intentions); [2], [37], [43] (epidemics) behavioural [34], [29], [41], [35], [28], [9] (organisation); [49], [57], [62] (ecological) temporally global agentbased internal [47], [24], [25], [64], [63], [48] (requirements); [31], [50], [59], [4], [21], [6], [7], [10], [12], [40] (verification) behavioural clusterbased internal [24], [25], [34], [29], [30], [41], [36], [18], [55], [64], [65] (requirements, enterprise); [43], [2], [37] (epidemics); [49], [57], …”
Section: Discussion and Classification Of Existing Modelsmentioning
confidence: 99%
“…For example, linear or branching time temporal logic are appropriate to specify various agent (system) behavioural properties. Examples of formal requirement specification languages based on such variants of temporal logic are described in [9], [10], [14], [22]. However, for adaptive agents, it might be necessary to specify adaptive properties such as 'exercise improves skill' for which we have to explicitly express a comparison between different histories.…”
Section: Discussionmentioning
confidence: 99%
“…If the composition of the system with its environment is intended to achieve emergent properties E, then the requirements engineer should look for assumptions A about the environment and properties S of the system such that A and S jointly entail E. This approach puts NYAM in the same class of requirements methods as KAOS [15,16], the requirements reference approach of the Gunters, Jackson and Zave [17,18] and, to some extent, SCR [19][20][21]. We call the argument that the environment and the system jointly assure the emergent properties the systems engineering argument.…”
Section: Not Yet Another Methods (Nyam)mentioning
confidence: 99%
“…Dwyer et al [60] have found a list of eight patterns in temporal properties and in the KAOS project [15,45] goal-oriented refinement patterns have been identified. We intend to look at the problem frames identified by Jackson [18] to see if we can build a library of formally verified patterns, plus guidelines to recognise and use these patterns.…”
Section: Further Workmentioning
confidence: 99%